Management of uncommon disorders in pregnancy: Von Hippel–Lindau disease, Gitelman syndrome, and Nutcracker syndrome. (September 2017) - Merhi, Basma; Miller, Margaret; Lanis, Aviya; Katz, Brittany; Hsu, Tiffany; Tong, Iris
Uncommon renal disorders in pregnancy can be challenging to manage given limited evidence in the literature to guide management. We present a series of three uncommon renal disorders in pregnancy: Von Hippel–Lindau disease, Gitelman syndrome, and Nutcracker syndrome. Previously published case reports with differing outcomes offer some guidance to the management of these disorders in pregnancy. In this case series, we address the management of these syndromes during pregnancy and discuss the maternal and fetal outcomes. All three of our patients had good maternal and fetal outcomes, which will contribute to current data on maternal and fetal outcomes in these rare diseases, which is limited.